2015
DOI: 10.1681/asn.2015060687
|View full text |Cite
|
Sign up to set email alerts
|

Past Decline Versus Current eGFR and Subsequent ESRD Risk

Abstract: ABSTRACTeGFR is a robust predictor of ESRD risk. However, the prognostic information gained from the past trajectory (slope) beyond that of the current eGFR is unclear. We examined 22 cohorts to determine the association of past slopes and current eGFR level with subsequent ESRD. We modeled hazard ratios as a spline function of slopes, adjusting for demographic variables, eGFR, and comorbidities. We used random effects meta-analyses to combine results across studies stratified by cohort type. We calculated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
75
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 36 publications
2
75
1
2
Order By: Relevance
“…The predictive value of diabetes and magnitude of proteinuria in the model is in agreement with the observation that CKD progresses faster in patients with diabetes and those with more proteinuria (20). Finally, the contribution of GFR trajectory to the predictive model is consistent with a recent investigation, which reported that both current eGFR level and the eGFR trajectory were predictors of progression to ESRD in patients with CKD (21). If our observations are confirmed in a multicenter study, they may provide a basis for a more customized approach to planning AVF placement in patients with CKD.…”
Section: Discussionsupporting
confidence: 88%
“…The predictive value of diabetes and magnitude of proteinuria in the model is in agreement with the observation that CKD progresses faster in patients with diabetes and those with more proteinuria (20). Finally, the contribution of GFR trajectory to the predictive model is consistent with a recent investigation, which reported that both current eGFR level and the eGFR trajectory were predictors of progression to ESRD in patients with CKD (21). If our observations are confirmed in a multicenter study, they may provide a basis for a more customized approach to planning AVF placement in patients with CKD.…”
Section: Discussionsupporting
confidence: 88%
“…Our study evaluated ESRD outcomes on more than 12,000 individuals with single abnormal creatinine measurements who were captured into the KPSC creatinine safety program. We were able to demonstrate higher ESRD incidence rates among those who were captured into the safety program and still higher among those who had a repeated creatinine 14,24 Our findings demonstrate that a high-risk population for CKD was indeed identified while we were able to track pertinent practice patterns and CKD-related outcomes. The main assumption is that the program will lead to interventions that result in better overall CKD and CKDrelated care.…”
Section: Discussionmentioning
confidence: 64%
“…However, these definitions are arbitrary and lacking in substantial evidence to support these definitions proposed. Results from a meta-analysis of 22 cohorts showed that eGFR decline slope greater than 3ml/min /1.73m 2 /year over the first 3years of CKD was significant associated with risk of ESRD (adjusted HR 1.73, 95% CI, 1.50 to 2.00)[29]. Using the data from the Alberta Kidney Disease Network (AKDN), among a cohort of 529,312 adults, the adjusted ESRD risks were 1.45, 1.53, 1.63, 1.90, 1.7 for the corresponding absolute annual rate of eGFR decline of -1, -2, -3, -4, and -5 ml/min/1.73 m 2 /year, respectively[5].…”
Section: Discussionmentioning
confidence: 99%